Some Inequalities for Ï -Convex Functions - Faye, I. (Springer Science and Business Media B.V., 2021)
The main purpose of this article is to establish Karamata and Ostrowski type inequalities for Ï -convex functions. An alternative definition of Ï -convexity is also proposed in this paper. With the alternative definition, simpler proofs of Hermite-Hadamard and Karamata type inequalities are established. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.